Usefulness of a Tailored eHealth Service for Informal Caregivers and Professionals in the Dementia Treatment and Care Setting: The eHealthMonitor Dementia Portal - Schaller, Sandra; Marinova-Schmidt, Velislava; Setzer, Manuela; Kondylakis, Haridimos; Griebel, Lena; Sedlmayr, Martin; Grässel, Elmar; Maler, Juan Manuel; Kirn, Stefan; Kolominsky-Rabas, Peter (JMIR Research Protocols, 2016)
The European eHealthMonitor project (eHM) developed a user-sensitive and interactive Web portal for the dementia care setting called the eHM Dementia Portal (eHM-DP). It aims to provide targeted support for informal caregivers of persons with dementia and professionals.The objective of this study was to assess the usefulness and impact of the eHM-DP service in the dementia care setting from two user perspectives: informal caregivers and professionals.The evaluation study was conducted from June to September 2014 and followed a before-after, user-participatory, mixed-method design with questionnaires and interviews. The used intervention was the eHM-DP: an interactive Web portal for informal caregivers and professionals that was tested for a 12-week period. Primary outcomes for caregivers included empowerment, quality of life, caregiver burden, decision aid, as well as perceived usefulness and benefits of the eHM-DP. Primary outcomes for professionals involved decision aid, perceived usefulness, and benefits of the eHM-DP.A total of 25 informal caregivers and 6 professionals used the eHM-DP over the 12-week study period. Both professionals and informal caregivers indicated perceived benefits and support by the eHM-DP. In total, 65% (16/25) of informal caregivers would use the eHM-DP if they had access to it. Major perceived benefits were individualized information acquisition, improved interaction between informal caregivers and professionals, access to support from home, and empowerment in health-related decisions (PrepDM Score: 67.9). Professionals highlighted the improved treatment and care over the disease course (83%, 5/6) and improved health care access for people living in rural areas (67%, 4/6). However, there was no improvement in caregiver burden (Burden Scale for Family Caregivers) and quality of life (EuroQol-5D-5L) over the study period.Our study provides insight into the different user perspectives on an eHealth support service in the dementia treatment and care setting. These results are of importance for future developments and the uptake of eHealth solutions in the dementia domain and reinforce the importance of early user involvement. Turning to the primary target of the eHM-DP service, our findings suggest that the eHM-DP service proved to be a valuable post-diagnostic support service, in particular for the home-based care setting. Further research on a larger scale is needed to enhance the implementation in existing health care infrastructures.
EVALuna2:141